2014
DOI: 10.1111/mpp.12203
|View full text |Cite
|
Sign up to set email alerts
|

Reduced susceptibility to Fusarium head blight in Brachypodium distachyon through priming with the Fusarium mycotoxin deoxynivalenol

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Furthermore, recent studies are proving that new insights into plant-microbe interactions can be revealed using brachypodium; the mapping of non-host resistance in brachypodium to wheat stripe rust (Ayliffe et al 2013), as outlined above, is a key example. Another important example is the very recent study of Blümke et al (2014) on the brachypodium-FHB interaction. Although the effect of DON on eliciting defence gene expression has been demonstrated in both wheat (Desmond et al, 2008) and brachypodium (Pasquet et al, 2014), Blümke et al (2014) have identified a new role for this mycotoxin as an inducer of resistance to FHB in brachypodium, seemingly via a 'priming' effect.…”
Section: Future Prospects For Brachypodium As a Model For Cereal-pathmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies are proving that new insights into plant-microbe interactions can be revealed using brachypodium; the mapping of non-host resistance in brachypodium to wheat stripe rust (Ayliffe et al 2013), as outlined above, is a key example. Another important example is the very recent study of Blümke et al (2014) on the brachypodium-FHB interaction. Although the effect of DON on eliciting defence gene expression has been demonstrated in both wheat (Desmond et al, 2008) and brachypodium (Pasquet et al, 2014), Blümke et al (2014) have identified a new role for this mycotoxin as an inducer of resistance to FHB in brachypodium, seemingly via a 'priming' effect.…”
Section: Future Prospects For Brachypodium As a Model For Cereal-pathmentioning
confidence: 99%
“…Another important example is the very recent study of Blümke et al (2014) on the brachypodium-FHB interaction. Although the effect of DON on eliciting defence gene expression has been demonstrated in both wheat (Desmond et al, 2008) and brachypodium (Pasquet et al, 2014), Blümke et al (2014) have identified a new role for this mycotoxin as an inducer of resistance to FHB in brachypodium, seemingly via a 'priming' effect. The pretreatment of brachypodium with low concentrations of DON was been found to reduce the susceptibility to FHB by eliciting defence gene expression and altering host cell-wall composition.…”
Section: Future Prospects For Brachypodium As a Model For Cereal-pathmentioning
confidence: 99%
“…Although the fungal attack was recognized and the defence response was initiated, Brachypodium was unable to repel the infection by WT. A similar induction of PR genes has been described during infection by F. graminearum ( PR1 and PR2 ; Blümke et al ., ) and the Panicum mosaic virus (PMV, PR1–3 , PR5 ; Mandadi and Scholthof, ). In contrast, lox2 was down‐regulated on PMV infection, a result which could not be confirmed for Claviceps infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, DON has been described as a virulent factor because analyses using DON producer and non-producer isolates show differences in the pathogen biomass on B. distachyon. Interestingly, by applying DON pretreatment prior to F. graminearum infection, Blümke et al (2015) observed that DON induced the priming of the B. distachyon spikelet tissue, thus contributing to reduce susceptibility to FHB. Diamond et al (2013) evaluated the effects of DON on the viability of arabidopsis cells and observed that low DON concentrations do not kill cells due to the capacity of DON to disarm the apoptosis-like plant programmed cell death.…”
Section: Fusarium Species Studiesmentioning
confidence: 99%
“…Finally, not only leaves were used to assay the Fusarium pathogenicity but also other plant tissues like stem, stem nodes, leaf sheaths, and root were inoculated with both pathogens and all of them were susceptible to F. graminearum and F. culmorum (Peraldi et al 2011). Therefore, F. graminearum wild type and several mutants with deficient virulence were used to inoculate single florets of B. distachyon spikelets and disease symptoms were induced in them (Blümke et al 2015). Considering its participation in plant interactions, the mycotoxins produced by F. graminearum have also been evaluated.…”
Section: Fusarium Species Studiesmentioning
confidence: 99%